Students' Scientific Writing Skills With Disciplinary Literacy Instruction - Zulfah Zulfah; Senam Senam (Reforma : Jurnal Pendidikan dan Pembelajaran, 2022)
Scientific writing skills are a very urgent need for students. This study aims to show the effect of the implementation of disciplinary literacy instruction as a strategy for scientific writing skills. The population of the study is the senior high school in Sleman region with  quasi-experimental method. The results of two replications were analyzed and showed normal and homogeneous results. This indicates that there is no difference in the learning outcomes of the two classes and shows the similarity of the cognitive abilities of the two classes, so research may proceed. The treatment given was in the form of disciplining literacy habits in students by using articles that contained problem-solving. Data collection using authentic assessment was in the form of student laboratory work reports. The analysis technique used to analyze the effect of the implementation of disciplinary literacy instruction on scientific writing skills was ANOVA test analysis at 0.05 significance level. The results showed that the sig value below 0.05 that is 0.01. This number indicates that there is an effect of the implementation of disciplinary literacy instruction to the students' writing skills on the material of electrolyte and non-electrolyte solution in the first grade of senior high school.